2017
DOI: 10.1016/j.puhe.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The reach, adoption, and effectiveness of online training for healthcare professionals

Abstract: Traditionally the continued professional development of healthcare professionals is completed through classroom based educational courses, workshops, and conferences. These can prove costly and time intensive. Online learning is becoming increasingly common, is easy to access, and can save learners time which is important in a healthcare system where job demands are high and study leave is limited. Well-designed internetbased learning has been shown to be as effective as traditional classroom based learning in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…In the context of training, such as for one-time skill development or continuing education, additional studies have found opportunities for similar or even enhanced performance by learners, such as in the context of library instruction or health training (Hemmati et al 2013;Silk et al 2015). In the public health arena, online training has become increasingly popular such that studies may now be fully focused on the efficacy of online efforts (Colleran et al 2012;Webb et al 2017), which seek the promise of expanded and accelerated health worker training in underserved or under-resourced areas (Rowe et al 2005).…”
Section: B Types Of Engagement and Interactionmentioning
confidence: 99%
“…In the context of training, such as for one-time skill development or continuing education, additional studies have found opportunities for similar or even enhanced performance by learners, such as in the context of library instruction or health training (Hemmati et al 2013;Silk et al 2015). In the public health arena, online training has become increasingly popular such that studies may now be fully focused on the efficacy of online efforts (Colleran et al 2012;Webb et al 2017), which seek the promise of expanded and accelerated health worker training in underserved or under-resourced areas (Rowe et al 2005).…”
Section: B Types Of Engagement and Interactionmentioning
confidence: 99%
“…Behavioural science has been applied to pro-environmental behaviours (Osbaldson and Schott 2012, Bamberg and Rees 2015, Byerly et al 2018, however, in most cases, the application of theory has not been linked specifically to an intervention development framework, the use of the COM-B model and the BCW overcomes this. The evidence-based approaches to be used in this research have been successfully applied in other areas such as public health (Webb et al 2016a(Webb et al , 2016b(Webb et al , 2017 and are transferable to future studies to understand and influence rewilding behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…1. Technology -The Internet and gadgets have become parts of everyone's lives nowadays (Hoi, Sahoo, Lu, & Zhao, 2018 (Webb, Stockwell, & Chavez-Ugalde, 2017). Expenses incurred are mainly for paying the trainers.…”
Section: The Advantages and Acceptancementioning
confidence: 99%
“…4. Minimal staff needed (Webb et al, 2017) -Only a moderator from ILD UiTM is needed to conduct online training along with the speakers/trainers. As compared to face-to-face training, a staff has to be ready at the registration counter for room registration and check-ins purposes, an audiovisual staff has to be present at all times for recording purposes, the staff has to be available at the registration desks for registration at the training rooms, and a driver has to be ready to chauffeur participants or speakers/trainers from and to the airport (if required).…”
Section: The Advantages and Acceptancementioning
confidence: 99%